EVALUATION OF PROFESIONAL DEVELOPMENT PROGRAMS TO IMPROVE TEACHING QUALITY AT SMP NEGERI 1 SUKOSARI BONDOWOSO - sriyulianti, sriyulianti (Faculty of Administrative Science, Universitas Brawijaya, 2025)
The quality of education highly depends on the competence and professionalism of teachers, particularly in their ability to innovate and adapt to developments in educational technology. This is especially evident in rural schools, such as SMP Negeri 1 Sukosari in Bondowoso, where optimizing the evaluation system for professional development programs is essential and needs to be further examined to ensure a significant impact on improving teaching quality. This study aims to analyze the evaluation system of teacher professional development programs in enhancing the quality of learning at SMP Negeri 1 Sukosari, Bondowoso Regency. The research focuses on the planning, implementation, and outcomes of evaluations related to teacher professional growth.This study employs a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and document analysis, involving the principal, vice principal of curriculum, active teachers, and school supervisors as research subjects. The data were analyzed using the interactive model by Miles and Huberman, involving data reduction, data display, and conclusion drawing.